2017
DOI: 10.1038/ncomms14065
|View full text |Cite
|
Sign up to set email alerts
|

Observational evidence for cloud cover enhancement over western European forests

Abstract: Forests impact regional hydrology and climate directly by regulating water and heat fluxes. Indirect effects through cloud formation and precipitation can be important in facilitating continental-scale moisture recycling but are poorly understood at regional scales. In particular, the impact of temperate forest on clouds is largely unknown. Here we provide observational evidence for a strong increase in cloud cover over large forest regions in western Europe based on analysis of 10 years of 15 min resolution d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
134
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 144 publications
(146 citation statements)
references
References 44 publications
(74 reference statements)
6
134
1
5
Order By: Relevance
“…(Randerson et al, 2006), the direct and indirect effects of wind disturbances may contribute to the top of the atmosphere radiative forcing (O'Halloran et al, 2012). The direct effects, such as a reduction in leaf area index (Juárez et al,5 2008), transpiration (Negrón-Juárez et al, 2010), an increase in the surface albedo (Planque et al, 2017), and roughness (Zhu, 2008) have been shown to impact the regional climate, i.e., following the storm Klaus in 2009, cloud cover frequency was observed to decrease over Les Landes in Southwestern France (Teuling et al, 2017). The indirect effects include a reduction of the gross productivity by damage to the rooting system, increased tree mortality due to facilitating insect or pathogen outbreaks (Sturrock et al, 2011), or a change of the forest ecosystem by shifting canopy structure to an old-growth with short stature 10 (Lin et al, 2017).…”
Section: Wind Storm Disturbances and Their Climate Feedbacksmentioning
confidence: 99%
See 1 more Smart Citation
“…(Randerson et al, 2006), the direct and indirect effects of wind disturbances may contribute to the top of the atmosphere radiative forcing (O'Halloran et al, 2012). The direct effects, such as a reduction in leaf area index (Juárez et al,5 2008), transpiration (Negrón-Juárez et al, 2010), an increase in the surface albedo (Planque et al, 2017), and roughness (Zhu, 2008) have been shown to impact the regional climate, i.e., following the storm Klaus in 2009, cloud cover frequency was observed to decrease over Les Landes in Southwestern France (Teuling et al, 2017). The indirect effects include a reduction of the gross productivity by damage to the rooting system, increased tree mortality due to facilitating insect or pathogen outbreaks (Sturrock et al, 2011), or a change of the forest ecosystem by shifting canopy structure to an old-growth with short stature 10 (Lin et al, 2017).…”
Section: Wind Storm Disturbances and Their Climate Feedbacksmentioning
confidence: 99%
“…Furthermore, storm-induced disturbances are likely to provide feedbacks on climate through direct effects such as increasing greenhouse gas emissions (Lindroth et al, 2009), increasing surface albedo (Planque et al, 2017), and decreasing local cloud 10 frequency (Teuling et al, 2017) as well as indirect effects such as increased natural disturbances, a reduced logging rate in subsequent years, increased weathering, and increased C, N and cation leaching (Futter et al, 2011;Köhler et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…These differ for each land system per world region. A land system map for the baseline year 2000, which is based on census and remote sensing data (van Asselen and Verburg, 2012), can be seen in Fig. 3.…”
Section: The Clumondo Model and The Future Scenariomentioning
confidence: 99%
“…This model uses a land system classification instead of the more traditional land cover classification (van Asselen and Verburg, 2012). Land systems are described by a set of fractional land cover classes consisting of built-up, cropland, grassland, forest, and other land co-occurring in spatial simulation units of 9.25 × 9.25 km pixel.…”
Section: The Clumondo Model and The Future Scenariomentioning
confidence: 99%
See 1 more Smart Citation